Development of the Serious Illness Care Program: a randomised controlled trial of a palliative care communication intervention. Issue 10 (6th October 2015) - Bernacki, Rachelle; Hutchings, Mathilde; Vick, Judith; Smith, Grant; Paladino, Joanna; Lipsitz, Stuart; Gawande, Atul A; Block, Susan D
Abstract : Introduction: Ensuring that patients receive care that is consistent with their goals and values is a critical component of high-quality care. This article describes the protocol for a cluster randomised controlled trial of a multicomponent, structured communication intervention. Methods and analysis: Patients with advanced, incurable cancer and life expectancy of <12 months will participate together with their surrogate. Clinicians are enrolled and randomised either to usual care or the intervention. The Serious Illness Care Program is a multicomponent, structured communication intervention designed to identify patients, train clinicians to use a structured guide for advanced care planning discussion with patients, 'trigger' clinicians to have conversations, prepare patients and families for the conversation, and document outcomes of the discussion in a structured format in the electronic medical record. Clinician satisfaction with the intervention, confidence and attitudes will be assessed before and after the intervention. Self-report data will be collected from patients and surrogates approximately every 2 months up to 2 years or until the patient's death; patient medical records will be examined at the close of the study. Analyses will examine the impact of the intervention on the patient receipt of goal-concordant care, and peacefulness at the end of life. Secondary outcomes include patient anxiety, depression, quality of life, therapeutic alliance, quality of communication, and quality of dying and death. Key process measures include frequency, timing and quality of documented conversations. Ethics and dissemination: This study was approved by the Dana-Farber Cancer Institute Institutional Review Board. Results will be reported in peer-reviewed publications and conference presentations. Trial registration number: Protocol identifier NCT01786811 ; Pre-results.